2015
DOI: 10.3390/biom5032035
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Activate Tristetraprolin Expression through Induction of Early Growth Response Protein 1 (EGR1) in Colorectal Cancer Cells

Abstract: The RNA-binding protein tristetraprolin (TTP) promotes rapid decay of mRNAs bearing 3' UTR AU-rich elements (ARE). In many cancer types, loss of TTP expression is observed allowing for stabilization of ARE-mRNAs and their pathologic overexpression. Here we demonstrate that histone deacetylase (HDAC) inhibitors (Trichostatin A, SAHA and sodium butyrate) promote TTP expression in colorectal cancer cells (HCA-7, HCT-116, Moser and SW480 cells) and cervix carcinoma cells (HeLa). We found that HDAC inhibitors-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…These results are in accord with those performed in the Myc-driven B cell lymphoma mouse model where enforced TTP expression in B cells disables the maintenance of lymphomas in syngeneic transplant model [5]. Interestingly, a recent study reported links of histone deacetylase inhibitor (HDACi) activity to TTP, where treatment of colorectal cancer cells with HDACi activates the EGR1 transcription factor to induce TTP and provoke growth arrest [19]. Collectively, these findings suggest that developing new therapeutics that specifically stimulate TTP expression may be an avenue for treating patients with low-TTP expressing tumors.…”
Section: Discussionsupporting
confidence: 84%
“…These results are in accord with those performed in the Myc-driven B cell lymphoma mouse model where enforced TTP expression in B cells disables the maintenance of lymphomas in syngeneic transplant model [5]. Interestingly, a recent study reported links of histone deacetylase inhibitor (HDACi) activity to TTP, where treatment of colorectal cancer cells with HDACi activates the EGR1 transcription factor to induce TTP and provoke growth arrest [19]. Collectively, these findings suggest that developing new therapeutics that specifically stimulate TTP expression may be an avenue for treating patients with low-TTP expressing tumors.…”
Section: Discussionsupporting
confidence: 84%
“…Another article revealed that the down-regulation of EGR1-p21 expression provides a mechanism for improved hematopoiesis (89). Histone deacetylase (HDAC) inhibitors can reactivate EGR1 in various cell types, leading to decreased cell proliferation and increased cell apoptosis (90). HDAC recruitment may participate in the repressive mechanism that EGR1 directly represses myocyte enhancer factor 2 (MEF2) activity for treatment of cardiac disease (91).…”
Section: Pathogenesis Mechanism Of Aml By Egr1mentioning
confidence: 99%
“…Cancer has a high morbidity and mortality[1-4]. In China, with the improvement of the economy and the enormous change in lifestyle and eating habits, the morbidity and mortality of gastric cancer have increased annually.…”
Section: Introductionmentioning
confidence: 99%